Psychotria honbaensis, a new species of Psychotria (Rubiaceae) with bacterial nodules from Hon Ba Nature Reserve, southern Vietnam - Nguyen, Quoc Bao; Truong, Ba Vuong; Nguyen, Quoc Cuong; Tagane, Shuichiro; Pham, van Ngot; Quach, van Toan Em; Huynh, Huu Duc; Pham, Quoc Trong; Dang, Van-Son (Phytotaxa, 2025)
Psychotria honbaensis, a new species belonging to Psychotria, Rubiaceae from Hon Ba Nature Reserve, Khanh Hoa Province, is described as new to science. It is easily distinguished from the other species of Psychtoria in Vietnam and surrounding countries by its bacterial nodules on abaxial surface of lamina, ovate-triangular stipules, inflorescence with winged-peduncle, and yellowish flowers. A standard description, color plates, distribution, habitat, proposed conservation status, taxonomic notes, and the morphological comparison to similar species are presented.